Особенности магнитной о-звезды HD149438 - Глаголевский, Ю. В.
Investigated features of the magnetic field and other properties of the star HD149438. It is shown that this star corresponds to other known magnetic O-stars in all respects. At the same time, all known O-stars have the same properties as SrCrEu+Si+He-w+He-r objects, which allows us to assume their same origin and evolution. There are data on the fact that the hypotheses of the origin of magnetic stars from close binary systems discussed in the literature are not supported by observations.
Keywords: Магнитное поле